The giant diploid faba genome unlocks variation in a global protein crop - Jayakodi, Murukarthick; Golicz, Agnieszka A; Kreplak, Jonathan; Fechete, Lavinia I; Angra, Deepti; Bednář, Petr; Bornhofen, Elesandro; Zhang, Hailin; Boussageon, Raphaël; Kaur, Sukhjiwan; Cheung, Kwok; Čížková, Jana; et al. (Nature, 2023)
Increasing the proportion of locally produced plant protein in currently meat-rich diets could substantially reduce greenhouse gas emissions and loss of biodiversity1. However, plant protein production is hampered by the lack of a cool-season legume equivalent to soybean in agronomic value2. Faba bean (Vicia faba L.) has a high yield potential and is well suited for cultivation in temperate regions, but genomic resources are scarce. Here, we report a high-quality chromosome-scale assembly of the faba bean genome and show that it has expanded to a massive 13 Gb in size through an imbalance between the rates of amplification and elimination of retrotransposons and satellite repeats. Genes and recombination events are evenly dispersed across chromosomes and the gene space is remarkably compact considering the genome size, although with substantial copy number variation driven by tandem duplication. Demonstrating practical application of the genome sequence, we develop a targeted genotyping assay and use high-resolution genome-wide association analysis to dissect the genetic basis of seed size and hilum colour. The resources presented constitute a genomics-based breeding platform for faba bean, enabling breeders and geneticists to accelerate the improvement of sustainable protein production across the Mediterranean, subtropical and northern temperate agroecological zones.
Keywords: semena rostlinná; Plant Breeding; Genes, Plant; Crops, Agricultural; zeměpis; genom rostlinný; DNA Copy Number Variations; Genome, Plant; genetická variace; zemědělské plodiny; šlechtění rostlin; Genome-Wide Association Study; variabilita počtu kopií segmentů DNA; Genomics; retroelementy; Gene Amplification; Vicia faba; chromozomy rostlin; Geography; Chromosomes, Plant; Plant Proteins; Seeds; Retroelements; amplifikace genu; satelitní DNA; DNA, Satellite; Recombination, Genetic; rekombinace genetická; Diploidy; rostlinné geny; Genetic Variation; diploidie; celogenomová asociační studie; rostlinné proteiny; genomika